Lenalidomide and Dexamethasone for a Patient of POEMS Syndrome Presenting with Massive Ascites. (19th February 2014) - Ueda, Shuji; Yonemoto, Sayoko; Oka, Kazumasa; Fujii, Naohiko; Nakata, Keiichi; Matsunaga, Hitomi; Kataoka, Seiko; Iwama, Yuki; Narahara, Hiroyuki; Yasunaga, Yuichi; Inui, Yoshiaki; Kawata, Sumio
Abstract : POEMS syndrome is a multisystem disorder characterized by polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes. POEMS syndrome is a rare cause of refractory ascites. We report the case of a patient with POEMS syndrome presenting with massive ascites who was treated with very-low-dose lenalidomide and dexamethasone. A 57-year-old Japanese man was admitted to our hospital with pleural effusion, massive ascites, and leg edema. The diagnosis of POEMS syndrome was made based on the combination of the following findings: peripheral neuropathy, organomegaly, endocrinopathy, serum monoclonal protein elevation, skin changes, plasma VEGF elevation, and evidence of extravascular volume overload. Renal dysfunction induced by biopsy-proven renal involvement of POEMS syndrome was observed. Massive ascites of the patient dramatically diminished with long-time treatment of very-low-dose lenalidomide and dexamethasone. Lenalidomide seems to be a very promising therapy for POEMS syndrome presenting with extravascular volume overload such as edema, pleural effusion, and ascites. Very-low-dose lenalidomide might be effective especially for the patients with POEMS-related nephropathy.